Two step process for volatile fatty acid production from brewery spent grain: Hydrolysis and direct acidogenic fermentation using anaerobic granular sludge. (January 2021) - Castilla-Archilla, Juan; Papirio, Stefano; Lens, Piet N.L.
Graphical abstract: Highlights: Two step process coupled diluted acid hydrolysis with direct acidogenic fermentation. Hydrolysis released up to 0.44 g carbohydrates per gram dried brewery spent grain. Acidogenic fermentation of leachate by non-pretreated anaerobic granular sludge. Highest volatile fatty acid production (16.9 g COD/L, 93.0 % CODsol ) found at pH 6.0. Abstract: Brewery spent grain (BSG) is an industrial waste stream with large potential for biorefining purposes. This work evaluated the production of volatile fatty acids (VFAs) by a two-step process using BSG as renewable feedstock by combining a single direct hydrolysis step (without removing the acid or potential inhibiting compounds) with an acidogenic fermentation step of the carbohydrate rich leachate. For the first step, a thermal diluted acid hydrolysis was carried (20 min at 121 °C), using eighteen different combinations in terms of total solid (TS) of BSG (4, 7 and 10 % w/w) and H2 SO4 (0.0, 0.5, 1.0, 1.5, 2.0 and 3.0 % v/v). The 7.0 % TS of BSG and 1.5 % of H2 SO4 combination was the most efficient in terms of total carbohydrate recovery (0.44 g of total carbohydrates per gram of TS). For the second step, an acidogenic batch fermentation of the hydrolysate was performed using anaerobic granular sludge at five different pH conditions (uncontrolled pH from an initial pH 7.0, and constant pH controlled at 4.5, 5.0, 6.0 and 8.0). The highest VFAs concentration was obtained at pH 6.0 and reached 16.89 (± 1.33) g COD/L, composed of mainly (99.5–99.8 %) acetate and butyrate.